Hypoxia‐inducible factors as key regulators of tumor inflammation. Issue 12 (2nd November 2012) - Mamlouk, Soulafa; Wielockx, Ben
Abstract Low levels of oxygen or hypoxia is often an obstacle in health, particularly in pathological disorders like cancer. The main family of transcription factors responsible for cell survival and adaptation under strenuous conditions of hypoxia are the "hypoxia‐inducible factors" (HIFs). Together with prolyl hydroxylase domain enzymes (PHDs), HIFs regulates tumor angiogenesis, proliferation, invasion, metastasis, in addition to resistance to radiation and chemotherapy. Additionally, the entire HIF transcription cascade is involved in the "seventh" hallmark of cancer; inflammation. Studies have shown that hypoxia can influence tumor associated immune cells toward assisting in tumor proliferation, differentiation, vessel growth, distant metastasis and suppression of the immune response via cytokine expression alterations. These changes are not necessarily analogous to HIF's role in non‐cancer immune responses, where hypoxia often encourages a strong inflammatory response.